Penerapan Metode Reading To Learn (R2L) Dalam Mengasah Kemampuan Menulis Siswa Sekolah Dasar - Daniaty Daniaty; Popy Sigalingging; Wisman Hadi; Mara Untung (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Writing skills are essential in education and need to be developed from an early age to ensure academic success. However, many children face challenges in writing, whether it’s related to structure, vocabulary, or creativity. These difficulties can hinder their ability to effectively communicate their thoughts and ideas. To address this, the Reading to Learn (R2L) method presents a solution that can significantly enhance children’s writing skills. The R2L method is a comprehensive approach that combines both reading and writing activities in a systematic way, allowing children to understand various text structures and patterns that they can apply in their own writing.This article discusses how the R2L method is not only effective but also enjoyable for children. Unlike traditional teaching methods that are either teacher-centered or student-centered, the R2L approach emphasizes the importance of collaboration and interaction between the teacher and the students to build knowledge. The method encourages children to think critically and creatively, helping them transform their ideas into coherent written form.By using the R2L method, students not only improve their writing abilities but also gain confidence in expressing their thoughts and ideas clearly. This boost in confidence is essential for their overall development as learners. The application of the R2L method in classrooms provides an innovative and engaging way to teach writing, fostering both creativity and critical thinking skills. As such, the R2L method offers a valuable approach to developing writing skills in children, making learning both effective and fun.